The Effectiveness of Langsa City Tourism Office Public Comunication in Socializing the Implementation of Halal Tourism - Fachrizal; Sakhyan Asmara; Fikarwin (PT FORMOSA CENDEKIA GLOBAL, 2023)
There is not much public communication regarding the socialization of halal tourism in Langsa City and those carrying out the socialization still overlap between the provincial government and the regional government. From the research results it can be described that the Tourism Office has carried out socialization regarding halal tourism, but it is limited and not routine. The forms of socialization carried out include counseling for village officials, socialization through various Langsa City events, socialization through activities of the Islamic Sharia Service, and socialization through social media. As for the effectiveness of the socialization of halal tourism, overall or as expected it is certainly not effective, meaning that the desired results have not yet been achieved because in carrying out the socialization of halal tourism, the Langsa City Culture and Tourism Office experienced several obstacles, a number of these obstacles being the lack of facilities and infrastructure. socialization and also low public awareness and participation regarding government recommendations regarding halal tourism.